2021
DOI: 10.1016/j.mex.2021.101397
|View full text |Cite
|
Sign up to set email alerts
|

Performance testing and comparative study of natural radioactivity in soil samples using high purity germanium (HPGe) detector

Abstract: High Purity germanium (HPGe) detectors are found to be suitable for nuclear techniques for measuring radionuclides with very good energy resolution. Inter-comparison exercise is an important tool for external quality control that enables determination of the accuracy and uncertainty of detector measurement system. In this work, a comparative study of natural radioactivity in soil samples was conducted between the laboratory of Autorité nationale de Radioprotection et de Sûreté Nucléaire (ARSN), Burkina Faso an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…The pH value is the highest for TT2 and it is the lowest for TT8. The pH value of TT1 is higher than in previous studies because the pH value of perlite varies between 7.7 and 8.53 F I G U R E 2 Variations of activity concentrations of 226 Ra, 232 Th, 40 K and 137 Cs for some inorganic materials used in soilless agriculture.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The pH value is the highest for TT2 and it is the lowest for TT8. The pH value of TT1 is higher than in previous studies because the pH value of perlite varies between 7.7 and 8.53 F I G U R E 2 Variations of activity concentrations of 226 Ra, 232 Th, 40 K and 137 Cs for some inorganic materials used in soilless agriculture.…”
Section: Resultsmentioning
confidence: 80%
“…24 Furthermore, gamma-ray spectrometry was used to determine the radiological properties of the inorganic materials used in soilless agriculture activity. 40 K, respectively, reported in the scientific report. 45 The activity concentrations of 226 Ra, 232 Th, and 40 K for inorganic materials were compared from the previous studies as shown in Table 6.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…A nondestructive technology for determining the particular radioactivity concentration of natural and manufactured radionuclides is the high purity germanium detector (HPGe). The precision of the measurement is determined by the HPGe detector's performance parameters [1]. Laboratory circumstances, equipment, standards, and sample matrixes all influence performance [2].…”
Section: Introductionmentioning
confidence: 99%